Recent patterns of terrestrial net primary production in Africa influenced by multiple environmental changes. Issue 5 (17th July 2015) - Pan, Shufen; Dangal, Shree R. S.; Tao, Bo; Yang, Jia; Tian, Hanqin
Abstract : Terrestrial net primary production (NPP) is of fundamental importance to food security and ecosystem sustainability. However, little is known about how terrestrial NPP in African ecosystems has responded to recent changes in climate and other environmental factors. Here, we used an integrated ecosystem model (the dynamic land ecosystem model; DLEM) to simulate the dynamic variations in terrestrial NPP of African ecosystems driven by climate and other environmental factors during 1980–2009. We estimate a terrestrial NPP of 10.22 (minimum–maximum range of 8.9–11.3) Pg C/yr during the study period. Our results show that precipitation variability had a significant effect on terrestrial NPP, explaining 74% of interannual variations in NPP. Over the 30‐yr period, African ecosystems experienced an increase in NPP of 0.03 Pg C/yr, resulting from the combined effects of climate variability, elevated atmospheric CO2 concentration, and nitrogen deposition. Our further analyses show that there is a difference in NPP of 1.6 Pg C/yr between wet and dry years, indicating that interannual climatic variations play an important role in determining the magnitude of terrestrial NPP. Central Africa, dominated by tropical forests, was the most productive region and accounted for 50% of the carbon sequestered as NPP in Africa. Our results indicate that warmer and wetter climatic conditions, together with elevated atmospheric CO2 concentration and nitrogen deposition, have resulted in a significant increase in African terrestrial NPP during 1980–2009, with the largest contribution from tropical forests.